Empowering Elementary School Teachers through Best Practice Scientific Writing Assistance in Kembangan, Jakarta - Uswatun Hasanah; Edwita Edwita; Prayuningtyas Angger Wardhani; Ahmad Januar (PT. Intelektiva Global Nusantara, 2026)
This community service activity aims to improve the competence of elementary school teachers in writing scientific papers based on best practice learning in DKI Jakarta. The activity was carried out on May 21–25, 2026 at SDN Meruya Selatan 06, involving 30 participants consisting of teachers and principals from SDN Meruya Selatan 06, SDN Meruya Utara 08, and SDN Joglo 09. Problems faced by teachers include a low understanding of the systematics of writing scientific papers, difficulty linking learning practices with theory, limited time, low motivation to write, and a high administrative burden. The methods used included socialization, training, mentoring in compiling best practice articles, evaluation, and reflection. Mentoring was carried out through writing clinics and small group discussions. The results of the activity showed an increase in participants' understanding and skills in compiling scientific papers. As many as 91% of participants successfully produced drafts of best practice articles. This program is effective in supporting a culture of scientific literacy and continuous professional development of teachers.